PENGARUH PENAMBAHAN ARANG AKTIF TULANG IKAN PADA PAKAN TERHADAP GAMBARAN DARAH IKAN NILA (Oreochromis Niloticus) - Mauditia Azhari; Lia Handayani; Nurhayati Nurhayati (Jurnal TILAPIA, 2020)
tilapia (oreochromis niloticus) is one type of fish that has high economic value. however, the great potential and open development prospects, is not a guarantee that fish farming will run smoothly without problems (yogiswara, 2008). the aim of this study was to determine the effect of the addition of activated charcoal from fish bones to feed on the blood picture of tilapia (oreochromis niloticus. test fish seeds used an average weight of 3.4 ± 0.1 gram and a length of 5.6 ± 0.1cm with a total of 15 tails / container maintenance time is 57 days feeding is carried out by adlibitum of 5% with a frequency of 2 times a day at 08.00 and 17.00 wib the design used is a non factorial complete randomized design (crd) by applying 4 treatments and 3 times repetition: as treatment, among others, treatment a (0%), b (1%), c (2%), and d (3%). the best blood test results showed that the addition of activated fish bone char on the feed to the picture of leukocyte blood was found in treatment c (2%)by 80.6%, erythrocyte treatment d (3%) by 1.89%, hemoglobin treatment c (3%) by 8.9%, hematocrit treatment b (1%) by 38.4 %, and treatment d platelets (3%) by 90%.